Guided Imagery of Progressive Muscle Relaxation Techiques as Blood Glucose Control in Type 2 Diabetes Mellitus - Jenny Saherna; Agung Widianingsih (UrbanGreen, 2021)
Guided imagery a method of delivering a treatment that makes it easier for someone to follow the recommended orders practicically, by looking at the steps through clear illustrated guides. Progressive muscle relaxation technique (PMR) is one of the independent nursing interventions that is easy to do by looking at the guide through pictures. It aims to help control blood glucose levels. This therapy maximizes muscle and breathing exercises, this technique also has a good impact on reducing anxiety, stress, fatigue, improving sleep quality and quality of life of patients suffering from type 2 diabetes mellitus. The research method used pre-experimental design with static group comparison. the test results obtained a value of P=0.030 (P-Value <0.05) the meaning that there is an average difference in the results of blood glucose levels before and after in the treatment group and the control group, namely 131.13 mg/dl, before giving the PMR technique an average result of blood glucose is 304.63 mg/dl. The conclusion is that the PMR technoique is recommended for patients with type 2 diabetes mellitus to help blood glucose control.